PENDAFTARAN TANAH SISTEMATIS LENGKAP(PTSL) DAN AGRARIA MENGHADAPI TANTANGAN PADA ERA MODERN DI DESA CIAMIS - Munawir, Ahmad; Handayani, Rini Sri; Angelina, Riyanti; Azzahra , Naila Kamila; Mulyatiningsih, Yuni (Yayasan Education and Social Center, 2025)
Community Service Activities are very beneficial for the community, in this case the community of Cimanis Village, Sobang District, Pandeglang Regency, Banten Province. Legal counseling regarding land certificates and land dispute resolution carried out in Sobang, provides enlightenment, motivation and increases insight into Land/Agrarian Law, namely that important land rights are proven by land deeds/certificates as evidence that has legal force. Land has economic value, the more the need for land, the higher the value of the land, inevitably resulting in increasing land conflicts. In addition to legal problems, the community can register their own land rights through Pendaftaran Tanah Sistmatis Lengkap (PTSL), so that it can speed up the process of issuing Badan Pertanahan Nasional (BPN). The implementation method applied to solve the problem of land certificates as the basis for rights and proof of land ownership through seminars accompanied by questions and answers in legal counseling delivered in Sobang District to the Cimanis Village Community. The importance of proof of ownership of land rights as the right of the residents of Cimanis Village, so that it can be followed up through Badan Pertanahan Nasional (BPN).